Development of Learning Management Model by Integrating PhenoBL Approach and DTP to Promote Curriculum Knowledge, Innovative Thinking Ability and Achievement Motivation of Thai Pre-Service Teachers - Intasingh, Somkiart (ASEAN Journal of Education, 2023)
This research aims to (1) study problems and needs in learning management of Curriculum Design and Development (CDD) course, (2) develop learning management model by integrating Phenomenon – Based Learning (PhenoBL) approach and Design Thinking Process (DTP) and (3) study results of learning management model implemented. Participants were 3 groups – (1) target groups who gave data about problems and needs were 20 undergraduate students, 4 major instructors and 3 administrators, (2) target group who evaluated the quality of model was 6 experts and (3) experimental sample group was 30 second year undergraduate students from The Faculty of Education, Chiang Mai University (CMU), Thailand who registered for the CDD course in the first semester of 2018 academic year. This section of students had mixed majors. They were chosen by cluster random sampling. This research was operated based on research and development (R&D) process. Research findings found that (1) students did not have important basic knowledge and were assigned to a lot of tasks in each of the courses. Major instructors and administrators identified that course instructor must organize learning to enhance curriculum understanding and develop achievement motivation of students, (2) learning management model, developed by researcher, consisted of 6 components - (i) purpose, (ii) principles, (iii) process in 5 stages - considering phenomenon (CP), analyzing related knowledge (AK), designing innovation (DI), criticizing innovation (CI) and improving and presenting innovation (IPI), (iv) roles of the students and instructors, (v) learning media and resources, and (vi) measurement and evaluation of the learning which verified the quality at a high level and (3) results of model implementation - students had curriculum knowledge, innovative thinking ability, and achievement motivation after learning were higher than prior to learning at the .01, .05 and .01 level of significance in sequence. The results show that the learning management model, developed by researcher, possessed appropriateness and applied to use in developing students’ learning quality